Perlindungan Hukum Bagi Debitur: Menggali Aspek Eksekusi dan Jaminan Fidusia - Malma Purnama, Sherli; Marhaeningsih, Marhaeningsih; Agustin Wulandari, Ratih (Zaaken: Journal of Civil and Business Law, 2024)
In the Fiduciary Guarantee Law, there are provisions regarding the execution of fiduciary guarantee objects in article 15. Initially, the Fiduciary Guarantee Law gave executorial power to fiduciary guarantee certificates. This means that creditors can execute fiduciary collateral objects without going to court. However, this provision has been canceled by the Constitutional Court in Decision Number 18/PUU-XVII/2019. The Constitutional Court's decision states that the provisions regarding the executorial power of fiduciary guarantee certificates are contrary to the 1945 Constitution of the Republic of Indonesia. This is because these provisions give too broad authority to creditors to execute fiduciary collateral objects without going through court. For this reason, it is necessary to know the legal protection for debtors because in fiduciary guarantees, creditors are superior to debtors. This research method uses a normative method with a statutory approach.